Legal framework for the treatment of foreign investment, volume 1 & II : survey of existing instruments. (Washington, D.C. : The World Bank, 1992)
Progress report and background studies.
Includes bibliographical references (p. 185-229).
Keywords: Investments, Foreign -- Law and legislation